Life, death and the transformation of the Western jurisprudential tradition : a comparative critical analysis of constitutional, legislative and judicial strategies - Dunlop, Frank J. (Trinity College (Dublin, Ireland). School of Law, 2013)
A comparative analysis of the constitutional, legislative and judicial strategies employed in the intentional recalibration of the traditional Western embodiment of the principle of the sanctity of life in order to legitimate earlier than natural death.
Keywords: Law, Ph.D.; Ph.D. Trinity College Dublin.